2003
DOI: 10.1016/s0741-5214(02)75454-2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular suture versus cutdown for endovascular aneurysm repair: a prospective randomized pilot study1 1Competition of interest: none.

Abstract: The percutaneous technique decreases the invasiveness of endovascular therapy of aortic aneurysm and reduces operative time and time to ambulation. Complications were roughly equivalent in severity. The additional cost for the device appears to justify its use for this form of aneurysm treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
239
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(256 citation statements)
references
References 12 publications
4
239
2
9
Order By: Relevance
“…The technical success rate is usually lower in earlier studies or studies with small patient populations, whereas recent studies or studies with large patient populations usually have a technical success rate exceeding 90% (1,4,5,9). The current and previous studies confirm that, as experience with the closure devices increases, the technical success rate increases, and the complication rate decreases (5).…”
Section: Discussionsupporting
confidence: 52%
“…The technical success rate is usually lower in earlier studies or studies with small patient populations, whereas recent studies or studies with large patient populations usually have a technical success rate exceeding 90% (1,4,5,9). The current and previous studies confirm that, as experience with the closure devices increases, the technical success rate increases, and the complication rate decreases (5).…”
Section: Discussionsupporting
confidence: 52%
“…With proper training, interventionalists may be able to treat the majority of VCs percutaneously. A percutaneous strategy has several advantages, including the lack of general anaesthesia, more rapid mobilization and decreased in-hospital complications, such as wound infections [18,19]. In a study of 149 patients with a VC rate of 18%, Stortecky et al showed a similar clinical outcome in patients undergoing percutaneous management and patients without VCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…The numbers in our study are too small to allow meaningful determination of factors predisposing to treatment failure. Others, while failing to demonstrate a benefit in terms of wound complication rates, have reported a decrease in operative time and time to ambulation post-operatively with percutaneous EVAR versus those having an open cutdown [7,8]. We chose not to examine these variables in this series as we felt that the results of the earlier cases, when we were learning the procedure, would produce a false ''skewing'' of the data and would be futile, as others have already comprehensively proven this point [7,8].…”
Section: Discussionmentioning
confidence: 98%